The Spanish crisis evolution and the analysis of its economy variables (Vývoj finanční a nemovitostní krize ve Španělsku a vybraných makroekonomických veličin) - Žabka, Petr (2016)
This bachelor thesis debates the causes, evolution and consequences of the Spanish financial and real estate crisis that came not only to Spain in 2007 and 2008. As the crisis's development was influenced by the country's history, there is a chapter summarizing what had occurred before the crisis actually started. To prove how the economy was damaged and what the evolution of the problem looked like in the real world, I followed with analysing some of the economic variables. At the end, there are several solutions the Spanish government proposed and made. Consequently, I mentioned some ways that, I suppose, would prevent such problems in the future and I also included my explanation of why preventing similar crisis is such a complicated issue.